La voix, souffle de l'émotion Parole et chant à l'âge classique (XVIIe et XVIIIe siècles) - Schweitzer, Claudia (Langages, 2022)
The human voice is a fascinating instrument. Through speech, singing and declamation, it transmits not only ideas, but also the emotions of the person who emits it. For a long time, its expressiveness has interested people, theorists as well as practitioners, and different paths have been taken to define and describe it. Based on the deeply interdisciplinary thought of the classical age, this book describes how the voice was thought about at that time. Indeed, music and language present fundamental structural links, allowing for the confrontation of disciplines and the linking of different traditions, but these have weakened considerably over the course of history. In order to rediscover these links, this research makes use of texts and compositions by French grammarians, orators, poets, musicians and philosophers of the 17th and 18th centuries. The interdisciplinary approach allows us to rediscover an astonishing abundance of ideas, images and methods of which we are at the same time the heirs, and without which the experimental work of the 19th-century phoneticians would not have been possible. This work still determines our understanding of vocal expression today.